Pengaruh Implementasi E-filing terhadap Kepatuhan Wajib Pajak Orang Pribadi (KPP Pratama Majalaya) - Shelvi Shelvi (Business Administration Department - Universitas Katolik Parahyangan, 2019)
For more than a decade, the government has been actively modernizing the tax administration system to encourage the level of taxpayer compliance. This tax administration system focuses on fulfilling the obligation of payment and reporting by taxpayers who were previously submitted manually, switched to online through the official website of the Directorate General of Taxation. The easier process of payment and tax reporting is expected to help smooth the fulfillment of obligations accompanied by the greater the chance of achieving the target of receiving the State Budget. Therefore, this study aims to examine whether the modernization of tax administration, especially in terms of reporting Individual Notification Letter (SPT) through e-filing is able to improve taxpayer compliance or not. This is a quantitative research using survey as the method. Data collection was conducted by distributing questionnaires to 80 respondents who are registered taxpayers at Majalaya Small Tax Office. The results showed that the implementation of e-filing have a positive effect on taxpayer compliance. From the results of data processing also found the need for socialitation and assistance for taxpayers to master the use of e-filing.